Group identities in Kenyan SMS messages - Nancy Ong'onda; Peter Maina Matu; Omondi Oketch (Acta Academica, 2010)
Short Message Service (SMS) as a new form of Computer Mediated Communication (CMC) seems to dissolve interaction and social hierarchies, thus resulting in the emergence of social groups. To determine how SMS has resulted in the emergence of social groups, this article explores the issues of group identities and language use in Kenyan text messages. Group identities and language use are examined in terms of age, social hierarchy and gendered identity. An integration of social structures and linguistic structures is emphasised. The findings reveal that a “new” language which presents the group identity of the users has evolved through SMS. Group identities are determined through the social agents of SMS language.